Handbook of flotation reagents : chemistry, theory and practice : flotation of sulphides ores - Bulatovic, Srdjan M. (Elsevier, 2007)
45 years of research in one indispensable volume.
Keywords: Flotation reagents -- Handbooks, manuals, etc.; Sulfides -- Handbooks, manuals, etc.; Flotation -- Handbooks, manuals, etc.; elektronické knihy; electronic books